Effects of Climate Change and Human Activities on Runoff in the Headstream Areas of Tarim River Basin - Deng, Xiaoya; Long, Ai-hua; Ling, Hongbo; Deng, Mingjiang; Zhang, Shouping (Journal of Environmental Accounting and Management, 2026)
Based on the measured runoff and meteorological data over the past 50 years in the headstreams of the Tarim River, this paper not only discussed the variation characteristics of runoff and climate factors, but also analyzed the impacts of climate change and human activities on the surface runoff by using the nonparametric test, extrapolation of variance analysis and periodic superposition trend model. Results showed that air temperature and precipitation increased significantly with the obvious abrupt change in 1993 and 1990, respectively. Surface runoff from the headstreams of the Aksu River and Yarkand River was in an increasing trend with the abrupt change in 1993, in which year the turning point of the impact of the human activities on the headstream runoff did occur as well. In Hotan River, the decreasing trend was slight, and the abrupt change was not obvious. According to the extrapolation of variance analysis, the periods of the three headstreams (Aksu River, Yarkand River, and Hotan River) are 25, 23, and 24 years, respectively. The periodic superposition trend model showed that the climate change had increased the total stream flow of the mountain pass in Aksu River and Yarkand River since 1993, but in regard of the headstreams from the mountain pass to Alar, the impact of human activities on runoff was more significant than that of climate change.